Metadiseñadores: simbiosis de herramientas digitales e inteligencia artificial en el diseño arquitectónico (Monográfico) - Fraile Narváez, Marcelo Alejandro (2024)
Throughout the 21st century, we have witnessed a paradigmatic metamorphosis in the field of architectural design, based on innovation and the use of digital tools. This evolutionary process has led to the emergence of a generation of professionals identified as “metadesigners”, whose distinction lies in their interdisciplinary approach that amalgamates architectural creation with research. Perceptive to the pervasive influence of digital systems in the contemporary world, metadesigners are emerging as protagonists in the reconfiguration of professional practices. However, the most far-reaching change has manifested itself in recent months with the proliferation and exponential development of tools based on artificial intelligence (AI), which have revolutionized the process of generating images and designs in architecture. AI has demonstrated its capacity to conceive creative and innovative solutions, marking a real turning point in this field. Starting from these premises and based on the hypothesis that the intersection between AI and architecture is intrinsically transforming the design process, enhancing both communicative efficiency and design quality, this paper aims to investigate and evaluate the effectiveness and efficiency of these processes, considering their impact on the quality and originality of the designs. Finally, this analysis aims to deepen the understanding of the emerging dynamics between AI and architecture, in order to continuously enrich this field and its relationship with contemporary society.